On Domatic Energy of a Graph - K. B. Murthy; B. V. Dhananjayamurthy (International Journal of Mathematics And its Applications, 2017)
In this paper, Motivated by the partition energy and the minimum covering energy of a graph, we introduce domatic energy E_d(G), of a graph G.